2013
DOI: 10.1073/pnas.1313505110
|View full text |Cite
|
Sign up to set email alerts
|

GABA B autoreceptor-mediated cell type-specific reduction of inhibition in epileptic mice

Abstract: GABA B receptors (GABA B Rs) mediate slow inhibitory effects on neuronal excitability and synaptic transmission in the brain. However, the GABA B R agonist baclofen can also promote excitability and seizure generation in human patients and animals models. Here we show that baclofen has concentration-dependent effects on the hippocampal network in a mouse model of mesial temporal lobe epilepsy. Application of baclofen at a high dose (10 mg/kg i.p.) reduced the power of γ oscillations and the frequency of pathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 51 publications
5
36
0
Order By: Relevance
“…In 4 of 4 post-SE AC-IN→FS-BC pairs, we found that SCH50911 reduced paired pulse ratio (i.e., increased paired pulse depression; IPSC2/IPSC1 in SCH50911 normalized to IPSC2/IPSC1 before SCH50911 perfusion: 70.3 ± 7.4%, P = 0.02, paired t-test, data not shown). Thus, our data are consistent with GABA B blockers increasing baseline synaptic release probability of the first IPSC and contributing to greater paired pulse depression of AC- IN→FS-BC synapses after SE and differ from the enhanced GABA B autoreceptors function observed in CA3 pyramidal cells after SE (Dugladze et al 2013).…”
Section: Post-se Increase In Gaba B Tone At Ac-in→fs-bc Synapsessupporting
confidence: 84%
See 4 more Smart Citations
“…In 4 of 4 post-SE AC-IN→FS-BC pairs, we found that SCH50911 reduced paired pulse ratio (i.e., increased paired pulse depression; IPSC2/IPSC1 in SCH50911 normalized to IPSC2/IPSC1 before SCH50911 perfusion: 70.3 ± 7.4%, P = 0.02, paired t-test, data not shown). Thus, our data are consistent with GABA B blockers increasing baseline synaptic release probability of the first IPSC and contributing to greater paired pulse depression of AC- IN→FS-BC synapses after SE and differ from the enhanced GABA B autoreceptors function observed in CA3 pyramidal cells after SE (Dugladze et al 2013).…”
Section: Post-se Increase In Gaba B Tone At Ac-in→fs-bc Synapsessupporting
confidence: 84%
“…Indeed, GABA B R are expressed in several classes of dentate interneurons including those expressing somatostatin, calretinin, and NPY (Sloviter et al 1999) and could undergo cell-type-specific changes in expression levels in these interneuronal populations following SE. Our demonstration of post-SE increase in GABA B -mediated suppression of FS-BC synaptic inhibition is consistent with recent findings in CA3 pyramidal cells in a mouse model of epilepsy (Dugladze et al 2013).…”
supporting
confidence: 92%
See 3 more Smart Citations